INTERNET PROGRAM AS A COMPONENT OF IMPROVING COMPETITIVENESS OF EDUCATIONAL ORGANIZATIONS: FROM MODELING TO IMPLEMENTATION - V. Vakulenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article analyzes the modern trends of using the Internet as a tool for improving the competitiveness of the educational organization. The article deals with the theoretical aspects of interactive technologies in educational organizations and presents a model of the process of developing Internet program of promotion educational service and suggests practical ways to implement the resulting stochastic model.